Perancangan Mesin Air Handling Unit (AHU) Untuk Ruangan Motor Control Center - Syarifuddin, M. Arvin (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
Motor Control Center (MCC) room is a room used to store electrical equipment. The temperature and humidity of the MCC room must always be maintained in order to ensure that the electrical equipment inside is not damaged. NFPA 70 B 2013 edition page 23 concerning athmosphere and environment recommends that the MCC room temperature ranges from 15 °C – 25 °C with air humidity between 40% - 65%. An HVAC (Heating Ventilating & Air Conditioning) system is needed to maintain temperature, humidity and filter the air from pollutants that enter the MCC room. In this design process the designer used 1 design method, namely the French Method, while the HVAC capacity calculation analysis refers to ASHRAE 1980, GRP 158 concerning cooling load calculations. The results achieved were to cool and maintain the condition of the MCC room with a volume of 213.2 m³ and the peak cooling load at 14.30 which was around 150,000 Btuh/43.96 KW. The design of the HVAC unit used has a capacity of 200,000 Btu/h (58.61 KW) taking into account the additional heat in the future, the exhaled air speed is 6,400 cfm, tsp 500 pa, equipped with an electric motor driving the blower with a capacity of 3 HP/4 phole/1700 Rpm/3 ph, Pully Motor 5.5" B2 x Pully Blower 10" B2, Evaporator Blower type VFD 400/950 rpm, V-belt type B with belt length 50", Evaporator Coil tube dimensions ᴓ 3/8” x 5 row Thickness x 46 Tube height x 13 fpi x 10000 mm Fin length, Angle iron frame galvanized 40 x 40mm,3.5 mm thickness, cover unit SUS 306. HVAC unit made of 2 units operating simultaneously changing as needed and equipped with thermostat control capacity to maintain room temperature of 15°C – 25°C.